Alterações fisiológicas da visão do idoso: construção de cenário de simulação clínica - Cordeiro, Tattiana Dias de Carvalho (2019)
Introduction: In the aging process, alterations of the sensory organs are considered important parameters in the evaluation of the life of the elderly, which stand out the visual acuity. Objective: To construct a scenario about physiological changes in the elderly's vision in the aging process. Method: Study developed in three stages: the first, integrative literature review; the second, fieldwork with the elderly and professionals; and the third, construction of the simulation scenario about visual acuity. The project was approved by the Ethics Committee of the Federal University of Paraíba. Results: The Integrative Literature Review was conducted in English, Portuguese and Spanish, in the National Library of Medicine National Institutes of Health, Cumulative Index to Nursing and Allied Health Literature, Embase Indexing and EMTREE and Scopus databases. A total of 778 articles were listed, including five articles in the final phase of the study. The changes and the causes of visual acuity were evidenced. In the Focus Groups there was a predominance of females, 95% in the Elderly Group and 66.6% in the professional group. Regarding the fieldwork, in the word cloud evaluation, the two Focus Groups outlined vision (f = 24); difficulty (f = 23); see (f = 22); cataract (f = 22); glasses (f = 19); surgery (f = 17); plus (f = 14); age (f = 13); eye (f = 12) and not (f = 11) and in the maximal tree we highlight the formation of nodes (nuclei), visual and deficiency. In the construction of the scenario it was proposed a medium fidelity simulation model that will have four participants in the teaching-learning process. Study Considerations: Building a simulated scenario on physiological changes in vision in the elderly provides learners with the opportunity to interact with the elderly and at the same time experience experiencing the difficulty of visual acuity in aging through the old age simulator.